Pengaruh Influencer Marketing terhadap Minat Beli Produk Skincare Ms Glow: - Tarigan, Ertika Br; Nofiawaty, Nofiawaty; Rosa, Aslamia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine the impact of influencer marketing on purchase intention for MS Glow skincare products, both simultaneously and partially. This quantitative study used a primary data obtained by distributing questionnaires to 100 respondents. The sampling technique used in this study was a purposive sampling technique. The analysis techniques used in this study are descriptive analysis, the F test, the T test, and multiple linear regression. This study showed a result that influencer marketing simultaneously has a significant impact on purchase intention. Authenticity and content partially have a significant impact on purchase intention. Brand fit and community partially have no impact on purchase intention. The multiple linear regression analysis showed a result that content has a dominant impact on purchase intention. Keyword: authenticity, brand fit, community, content, purchase intention